Desmopressin in combination with anticholinergic agents in the treatment of nocturnal enuresis: a systematic review and meta-analysis - Cai, Tong; Yao, Yi; Sun, Weigui; Lei, Peipei (Frontiers in Pediatrics, 2023)
The desmopressin combined with anticholinergic agents for the treatment of nocturnal enuresis (NE) remains controversial. This meta-analysis assesses the efficacy and safety of desmopressin compared with desmopressin plus anticholinergic agents for the treatment of nocturnal enuresis (NE) at least 1-month treatment cycle. Eight studies involving 600 patients (293 in the combination group and 307 in the desmopressin group) contained meaningful data.The results were as follows: after one month of treatment, compared with the desmopressin monotherapy group, the combination group was significantly better in treating NE in FR (full responders, P=0.003), FR+PR (partial responders) (P<0.0001), and the mean number of wet nights ( P=0.004); also, the combination group had a better effect in FR(P<0.00001), FR+PR (P=0.02) and the mean number of wet nights ( P=0.04) after 3 months' treatment. For side effects, combination therapy does not cause more adverse events in treating NE (P=0.42). This study elucidates that desmopressin combined with the anticholinergic agent was demonstrated to be more effective in treating NE than desmopressin monotherapy, and the anticholinergic agent does not increase the risk of adverse events (AEs).